Diagnosis of Ischemic Colitis. Case Report - Vivianne Anido Escobar; Elizabeth Fernández Tamayo (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Ischemic colitis is the most common form of intestinal ischemia. It is frequently observed in patients older than 65 years, and the risk factors of the disease are already known. Objective: To consider the early diagnosis of the disease in a patient in whom risk factors for the disease are identified after performing specific diagnostic tests. Case Presentation:  A patient with rectal bleeding is presented. On questioning and physical examination, risk factors for ischemic colitis are identified. The diagnosis is confirmed by colonoscopy, and the radiological tests permitted to identify the cause and location of the ischemia. Conclusions: The identification of risk factors for ischemic colitis allowed to think on the possibility of the disease. Diagnostic tests, performed in an early period, confirmed the diagnosis and made a good response to treatment possible. Keywords: Ischemic colitis, emergency colonoscopy, colonoscopy with CO2, CT angiography, emergency angiography, risk factors.